A complex conceptualization of beauty in Latinx women: A mixed methods study. (June 2022) - Gruber, Elisabeth; Kalkbrenner, Michael T.; Hitter, Tracie L.
Abstract: Latinx women face a myriad of unique pressures to meet unrealistic standards of beauty that are not captured in the dominant, Eurocentric framework of beauty and body image in the U.S. The majority of the extant body image literature represents the experiences of White women and overlooks salient body areas that women of color may experience dissatisfaction with. The present researchers employed a convergent-parallel mixed methods design to examine demographic differences as well as the lived experiences of Latinx women's relationship with beauty and their bodies. Quantitative results from 118 participants revealed that Latinx women with an annual income< 60k (54.2%) reported a higher discrepancy between their actual and ideal buttock size compared to Latinx women with an annual income> 60k (45.8%). Furthermore, a thematic analysis revealed four emergent themes that reflected the unique perceptions and lived experiences of 98 Latinx women's experiences with body image. Findings may assist clinicians working with Latinx women, as they will be able to better understand and integrate relevant cultural aspects of body dissatisfaction when working with Latinx clients. Highlights: Latinx women's perceptions of the body ideal may depart from Eurocentric standards. Latinx women that made 60, 000 annually experienced more body dissatisfaction. Hourglass, curvaceous body ideal preference. Dissatisfaction with other body areas such as skin tone and nose size.